2002
DOI: 10.1007/s00441-002-0610-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, immunohistochemical characteristics and nerve pathways of primary sensory neurons supplying the porcine vas deferens

Abstract: The present study investigated: (1) the distribution and chemical coding of primary sensory neurons supplying the vas deferens in juvenile pigs by the use of retrograde tracing combined with double-labelling immunofluorescence, (2) nerve pathways from dorsal root ganglia (DRG) to the vas deferens by means of denervation procedures involving transection of the hypogastric or pelvic nerve combined with a retrograde tracing method, and (3) possible interactions of the substance P (SP)/calcitonin gene-related pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 27 publications
3
32
0
Order By: Relevance
“…A bilateral positivity in SGs has been observed in some genital organs, such as the vas deferens of the rat (Kolbeck and Steers, 1993) and of the pig (Kaleczyc et al, 2002) and the retractor penis muscle of the pig (Panu et al, 2003). The sacral extension of marked SGs found in this study confirms that also in the pig the afferent fibres from BSM travel along the pudendal nerve.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…A bilateral positivity in SGs has been observed in some genital organs, such as the vas deferens of the rat (Kolbeck and Steers, 1993) and of the pig (Kaleczyc et al, 2002) and the retractor penis muscle of the pig (Panu et al, 2003). The sacral extension of marked SGs found in this study confirms that also in the pig the afferent fibres from BSM travel along the pudendal nerve.…”
Section: Discussionsupporting
confidence: 85%
“…6 red and blue lines). Numerous morphological and physiological studies have revealed that CMGs and PGs receive and integrate nervous inputs originating from different sources, including sympathetic preganglionic, viscerofugal enteric and spinal sensory neurons (Simmons, 1985;Keast, 1999;Majewski, 1999;Bossowska, 2002;Kaleczyc et al, 2002). In particular, these spinal afferents may influence the activity of postganglionic autonomic neurons both directly (through their collaterals within the CMGs or PGs) and indirectly (through axonal collaterals forming synaptic contacts with either preganglionic autonomic neurons in the intermedio-lateral nucleus or interneurons within the dorsal horn) (Keast, 1999;Majewski, 1999;Bossowska, 2002;Kaleczyc et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For several years, our research group has been studying the site and immunohistochemical characteristics of the peripheral and/or central neurons related to smooth and striated muscles of the genital organs of the male pig, that is frequently used as a model in biomedical research (Dodds, 1982;Swindle et al, 1992;Crissinger et al, 1994), including neuroanatomical studies (Merighi et al, 1990;Majewski and Heym, 1992;Timmermans et al, 1993;Panu et al, 2001;Bossowska, 2002;Kaleczyc et al, 2002;Panu et al, 2003;Botti et al, 2006aBotti et al, ,b, 2009. Our localization studies (Bo Minelli et al, 2000Botti et al, 2003;Panu et al, 2003;Botti et al, 2006bBotti et al, , 2009) have constantly documented that the peripheral sensory and autonomic neurons, innervating the aforesaid muscles, are rather numerous and located in very similar peripheral sites.…”
Section: Introductionmentioning
confidence: 99%